Impact of bay breeze and thunderstorm circulations on surface ozone at a site along the Chesapeake Bay 2011–2016 - Mazzuca, Gina M.; Pickering, Kenneth E.; New, David A.; Dreessen, Joel; Dickerson, Russell R. (Atmospheric environment (1994), 2019)
Coastal regions are frequently subject to higher concentrations of ozone (O3) than areas farther inland due to thermally-direct recirculation (e.g., sea/bay breezes) of pollutants during summer months. Along with high O3 concentrations on polluted days, a bay breeze (in this case, the Chesapeake Bay breeze) causes low-level convergence over the land, which can lead to deep convection even on days without any large-scale convective forcing, altering both the local flow pattern and the concentrations and distributions of pollutants. Presented here is a bay breeze and thunderstorm climatology for Edgewood, MD, a coastal site along the Chesapeake Bay, from June, July, and August 2011–2016 between 11 and 19 EST (UTC-5). Using meteorological data from the Maryland Department of the Environment (MDE), bay breezes are identified by an automated detection algorithm, the Bay-breeze Identification Algorithm (BIA), customized for the complex coastline of river inlets within the Chesapeake Bay area. Additionally, thunderstorm vs. non-thunderstorm days are analyzed using gridded Earth Networks lightning data (ENTLN) within an influential radius of the site. The effects of bay breezes and deep convection on local O3 is quantified. The highest daily conditional mean O3 for all years was observed on bay breeze days, and the lowest on days with thunderstorms only (no bay breeze). Additionally, 39% of O3 exceedance days within the analysis time period were also bay breeze days. However, as ozone precursor emissions have fallen, the relationship between bay breezes and high O3 has diminished. While days with thunderstorms only (no bay breeze) were associated with the lowest daily mean O3, there were O3 events on some thunderstorm days, especially if there was also a bay breeze. Twenty-four percent of the total ozone exceedance days had a thunderstorm, demonstrating that thunderstorm days should not be assumed to be clean days, as boundary-layer venting and downdraft mixing depends on the thunderstorm duration and type (e.g., non-frontal/pop-up convection allowed slightly higher O3 concentrations than did frontal convection). These results illustrate the significant role that localized meteorological events that are difficult to predict play in modulating air pollution where many of the world's cities lie – near bodies of water. •Mean O3 concentrations are higher on bay breeze days than on non-bay breeze days.•Thunderstorms do not always terminate a pollution episode.•The relationship between bay breezes and O3 episodes diminishes with cleaner air.